Best Answer

All that you can do is to simplify the left hand side of the "equation" to the expression 2x + 6y + 1.

Since the right hand side of the original "equation" is not given, it is, in fact an expression and cannot be solved. In any case, one linear equation in two variables cannot be solved.

Q: How do you do 5x plus 6y plus 4-3x-3 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The question contains two equations:5x - 6y = 15 5x + y = 2 There are no inequalities in the question.

(3, 3)

the simplest form of 5x + 3y +2x - 6y is 7x-3y

3x + 6y = 48 .... Eq.1-5x + 6y = 32 .... Eq.2 .... in another way 6y = 5x + 32Put the value of Eq.2 in Eq. 13x + 5x + 32 = 488x = 48 - 328x = 16x = 16/8 ...... X = 2To find the value of Y put the value of X in Eq.26y = 5x + 326y = 5(2) + 326y = 10 + 326y = 42y = 42/6 ...... Y + 7

- 5x - 6y - 8 = 0Add (5x + 8) to each side:- 6y = 5x + 8Divide each side by -6 :y = (-5/6)x - 8/6y = - 5x/6 - 4/3

Related questions

-5x + 6y = 24 6y = 5x + 24 y = 5/6 x + 4 the slope is 5 6

The question contains two equations:5x - 6y = 15 5x + y = 2 There are no inequalities in the question.

yes it is!

(4, -2)

(3, 3)

-5/6

(3,3)

-5x + 6y = 30At the x-intercept, y=0:-5x = 30 ==> x = -6At the y-intercept, x=0:6y = 30 ==> y = 5

the simplest form of 5x + 3y +2x - 6y is 7x-3y

There are 2 unknowns

5x -6y=-30 5x-6y=30 (2x+3y) (2x-3y)=30 4x+6y=30 4x=30 x=30/4

3x + 6y = 48 .... Eq.1-5x + 6y = 32 .... Eq.2 .... in another way 6y = 5x + 32Put the value of Eq.2 in Eq. 13x + 5x + 32 = 488x = 48 - 328x = 16x = 16/8 ...... X = 2To find the value of Y put the value of X in Eq.26y = 5x + 326y = 5(2) + 326y = 10 + 326y = 42y = 42/6 ...... Y + 7